The association of tobacco marketing with median income and racial/ethnic characteristics of neighbourhoods in Omaha, Nebraska. Issue 3 (15th April 2010) - Siahpush, Mohammad; Jones, Pamela R; Singh, Gopal K; Timsina, Lava R; Martin, Judy
Abstract : Objective: To examine the association of point-of-sale tobacco marketing with median income and racial/ethnic composition at the neighbourhood level in Omaha Metropolitan Area, Nebraska. Methods: Fieldworkers collected comprehensive tobacco marketing data from all of the stores that were licensed to sell tobacco in 84 randomly selected neighbourhoods in the Omaha Metropolitan Area, Nebraska. Results: An increase of $10 000 in median household income was associated with a decrease of 14.3% in the number of tobacco marketing items per square mile in a neighbourhood (p=0.021). There was very little evidence that the percentages of African-American and Hispanic populations in the neighbourhoods were related to tobacco marketing. Conclusion: Banning tobacco marketing, as recommended by the Framework Convention on Tobacco Control, is likely to reduce tobacco use disparities.